A Lesson Design on the Subject of Climate Change as a Course Unit in Language Teaching - Coskun, Hasan (Journal of Education Culture and Society, 2024)
Aim. The purpose of this qualitative research is the preparation, implementation and evaluation of a present-related lesson focused on the selection of the subject of climate change for elective German courses taught in universities. For climate change, the issues of sustainability and peace are also important. It is important to address these issues in educational institutions. The dove of peace is an important figure.Methods. In this research the document analysis technique was used. The research on the subject of climate change, sustainability and peace in the context of relation to the present was taken up during the winter semester of 2022/2023 academic year in the elective German courses of the researcher at Hacettepe University.Results. The successful contribution of the lesson planning model already mentioned in this article was also observed in the teaching activities at primary and secondary schools conducted earlier. The participants discussed climate change, sustainability, and peace.Conclusion. It was observed that the participants voluntarily talked about climate change, sustainability, and peace. It is important to state that the interest of the participants in German courses continued.Originality. German language courses are offered as a foreign language learning practice and elective foreign language courses in schools, private institutions, and universities in Turkey. Participants from all the departments of the Hacettepe university voluntarily attended the elective German language classes. To conduct the German courses effectively, a suitable method should be developed to help the participants who come from different countries having various levels of fluent speech.